PARENTING PERAN ORANG TUA DALAM MENSTIMULASI MOTORIK UNTUK MENGEMBANGKAN KREATIVITAS ANAK DI PAUD MANTRIWIRYA SURABAYA - Ery Rahmawati; Anggralita Sandra Dewi; Eni Nurhayati; Galuh Kartika Dewi (STKIP PGRI Sidoarjo, 2022)
This parenting activity is motivated by the reality faced in the field that the lack of parental roles in stimulating children's motor skills so that children's creativity is less developed. This condition is caused by a lack of parental knowledge in stimulating children's motor skills. The purpose of this service is to provide insight into parenting patterns in developing motor skills for children aged 3 to 6 years. The material chosen is parenting or counseling activities that focus on motor development and the role of parenting at home in order to develop children's creativity. The equipment and materials used are LCD as a means of counseling. This parenting activity is carried out at PAUD Mantiwirya Surabaya. Overall, this activity went well and parents understood the importance of stimulating their children's motor skills from an early age and parents knew that their children were capable of imagining to create creativity.